Comparative Study in Zebrafish and Medaka Unravels the Mechanisms of Tissue Regeneration - Chowdhury, Kaushik; Lin, Shi; Lai, Shih-Lei (Frontiers in Ecology and Evolution, 2022)
Tissue regeneration has been in the spotlight of research for its fascinating nature and potential applications in human diseases. The trait of regenerative capacity occurs diversely across species and tissue contexts, while it seems to decline over evolution. Organisms with variable regenerative capacity are usually distinct in phylogeny, anatomy, and physiology. This phenomenon hinders the feasibility of studying tissue regeneration by directly comparing regenerative with non-regenerative animals, such as zebrafish (Danio rerio) and mice (Mus musculus). Medaka (Oryzias latipes) is a fish model with a complete reference genome and shares a common ancestor with zebrafish approximately 110-200 million years ago (compared to 650 million years with mice). Medaka shares similar features with zebrafish, including size, diet, organ system, gross anatomy, and living environment. However, while zebrafish regenerate almost every organ upon experimental injury, medaka shows uneven regenerative capacity. Their common and distinct biological features make them a unique platform for reciprocal analyses to understand the mechanisms of tissue regeneration. Here we summarize current knowledge about tissue regeneration in these fish models in terms of injured tissues, repairing mechanisms, available materials, and established technologies. We further highlight the concept of inter-species and inter-organ comparisons, which may reveal mechanistic insight and hint at therapeutic strategies for human diseases.